تعويض الزمن الميت في نظم التحكم باستخدام النموذج المرجعي التكيفي - محسن داؤود; بلال شيحـا; نعمى حسـن (Tishreen University, 2019)
لقد تمّ في هذا البحث معالجة مشكلة الزمن الميت التي تعد من أخطر المشاكل في النظم الحقيقية، لما تسببه من اضطراب لحلقة التحكم في نظم التحكم بالعمليات. تمت المعالجة بتعويض تأثير هذا الزمن بوساطة معوضات الزمن الميت(DTCs)    Dead Time Compensators، إذ تم اقتراح طريقة لتعويض التأخير الزمني تقوم على تكييف الربح مع زمن ميت  Gain Adaptive- Dead time Compensation  ، ومن ثم مقارنتها بالطرق السابقة التي تعاملت مع هذه المشكلة، كطريقة جيلز وبارتلي Giles And Bartley وطريقة سميث Smith Dead time-Compensation  . وقد أثبتت النماذج التمثيلية المقدمة فعالية هذه الطريقة وبينت نقاط القوة والضعف فيها وفقاً لتغير الشروط المحيطة، كما تضمن البحث تمثيلاً برمجياً simulation للطرق الثلاث مع عرض لمنحنيات استجابة الخرج وحساب قيمة الخطأ الزمني المطلق. This research addresses the problem of dead time, which is considered one of  the most danger problems in real systems, because of the disturbance it causes to the control loop in process control systems. Solving this problem was achieved by compensating the dead time effect by means of dead time compensators (DTCs). A  method for compensating dead time was suggested. It is based on compensating dead time by gain adaptive (GADC), then comparing it with previous methods that dealt with this problem, like Giles and Bartley method (G&B) and smith method (SDC). Representative models proved the viability of this method and displayed its strength and weakness points according to the changes in actuation conditions. The research consists programming presentation (simulation) for these methods and present output response curves, calculating the integrate time absolute error (ITAE).